Culture, cognition and academic achievement of Malay students in Singapore - Hashim Ali. (2009)
The dismal educational performance of the Singapore Malays has been an extensive area of research by several academicians. They lamented the low percentage passes at all levels of national examinations from Primary School Leaving Examination (PSLE) to General Certificate of Education at Advanced Level (GCE 'A'). Studies on High attrition rates among the Malays have been an area of concern among the educationists. However, this study looks at the issue from a different perspective. There is an ever increasing and sizeable number of Malay high achievers at every national examinations, namely at the Primary School Leaving Examination and the General Certificate of Education at both the Ordinary and the Advanced Levels (PSLE, GCE 'O' and GCE 'A' levels). They constitute the top ten per cent of each level in terms of academic achievement.